Blockage of TGF-β1-induced epithelial-to- mesenchymal transition by oxymatrine prevents renal interstitial fibrosis - Li Li; Dongyuan He; Qin Cai; Dong-ying Wang (Universidade de São Paulo, 2022)
Abstract Most chronic kidney disease inevitably progress to renal fibrosis. Tubular epithelial- to-mesenchymal transition (EMT) is recognized to play major roles in renal fibrosis. Oxymatrine (OM) is a major alkaloid component found in a Chinese herb Sophora roots and has many effects. The aim is to investigate the effect of OM on renal tubular EMT and elucidate its mechanism. Mice underwent unilateral ureteral obstruction (UUO) followed by intraperitoneal injection of OM (120 mg/kg) or control vehicle. Human kidney proximal tubular cell line (HK-2) was used and EMT was induced with 5 ng/mL of transforming growth factor-β1 (TGF-β1). In vivo, renal tubulointerstitial fibrosis was induced and E-cadherin was down-regulated, while the expressions of fibronectin (FN), α-smooth muscle actin (α-SMA), TGF-β1 and its type I receptor (TGF-βRI) were up-regulated in UUO mice. In contrast, OM significantly ameliorated renal fibrotic lesions and attenuated the expressions of FN, α-SMA, TGF-β1 and TGF-βRI, but increased E-cadherin in the obstructed kidneys. In vitro, OM abolished TGF-β1-mediated E-cadherin suppression and FN, α-SMA and TGF-βRI induction in HK-2 cells in a dose-dependent manner. These observations strongly suggest that the renal protective effects of OM could be mediated by prevention of EMT and manifested as suppression of TGF-β1 and TGF-βRI expressions.